Delayed-Interval Delivery in Multiple Pregnancy: A Single-Center Experience of Five Cases - Gadeer, Roaa Hassan; Alhinai, Ahlam; Fung-Kee-Fung, Karen; Werlang, Ana (American Journal of Perinatology Reports, 2024)
Objectives To describe the obstetric management and perinatal outcomes in multiple pregnancies with delayed-interval delivery (DID) of the cotwin in a tertiary hospital.Methods This is a retrospective chart review of all cases of DID between December 2021 and 2022 at The Ottawa Hospital. Five cases of DID were identified and reviewed to obtain information on obstetric management and maternal–neonatal outcomes. We included eligible twins and triplets. No multiples were excluded. We obtained ethics approval for this case series.Results Four sets of dichorionic diamniotic twins and one trichorionic triamniotic triplet were included. Our patients were admitted between 173/7 and 215/7 weeks of gestation. We achieved an interval delivery range between 1 and 36 days. Four out of six multiples did not survive in DID. The two surviving newborns were born at 230/7 and 232/7, stayed in the neonatal intensive care unit (NICU) for 111 and 131 days, discharged with a weight of 3,594 and 2,743 g, respectively. All DID cases were delivered spontaneously except for two patients that required augmentation due to maternal sepsis.Conclusion Despite the high risk of maternal, fetal, and neonatal morbidity and mortality, if delivery of the first twin occurs before 20 gestational weeks, DID could be considered in selected cases to improve outcomes for the cotwin.
Keywords: multiple; preterm birth; multiple pregnancy; premature; infant